Sociologija gledališča v dobi negotovosti tekočih družb - Toporišič, Tomaž (Družboslovne razprave, 2024)
he article looks at the possibilities for the sociology of theatre in an era of liquid modernity (Bauman), uncertainty, and individualism. Namely, the fields of rese- arch proposed by G. Gurvitch in the 1950s, J. Duvignaud in the 1960s, and M. Shevtsova and P. Pavis in the 1990s remain relevant today. However, sociology Tomaž ToporišičDRUŽBOSLOVNE RAZPRAVE/Social Science Forum, XL (2024), 105–106: 209–227210 of theatre must engage in a dialogue with cultural studies (R. Williams, S. Hall), critical social theory (T. W. Adorno), gender and sexuality studies (J. Dolan), postcolonial studies (E. Said/G. Spivak), race studies (H. Young), reception studies (H. R. Jauss), and the renewed semiotic of Fischer-Lichte in the aesthetics of the performative. By taking these steps, the sociology of theatre can provide insights into the dynamic relationship between theatre and society.
Keywords: kulturologija; moderna družba; sociologija gledališča; sociosemiotika; tekoča moderna; uprizoritvene prakse